Memorandum of understanding for cooperation between the Fundação Minerva - Cultura – Ensino e Investigação Científica / Universidades Lusíada and the Center for Strategic Research of the Ministry of Foreign Affairs of the Republic of Turkey - Fundação Minerva - Cultura - Ensino e Investigação Científica (2015)
Maintain an active exchange of information about their activities; - Exchange information related to activities of common interest, taking into consideration possible joint participation in meetings of bilateral, regional and international character; - Facilitate the exchange of their monographs, research, papers, periodicals, and other pertinent and electronically published material on topics relevant to issues of scientific and mutual interest; - Consult on the possibilities of organizing conferences, round-tables, symposia, panels and discussions, brain-storming session and seminars that could be alternately in Turkey and Portugal such activities could also be organized with the participation of third parties; - Facilitate the exchange of conference speakers, experts and researchers